Intelligent Traffic Control System Design Based on Single Chip Microcomputer - Lei, Xu; Sheng, Ye; Guilin, Lu; Zhen, Zhang (Information and Management Engineering, 2011)
This paper mainly introduces microcontroller of counter to implement an intelligent traffic control system. The system uses an external triggered pulses to simulate, through traffic to timing/counter car collection, so as to realize the flow of traffic information digitization. Meanwhile, according to historical stored data and automatic detection to car traffic information, microcontroller will be compared, and the control model algorithm control scheme by setting proper signal ratio, realizing the intelligent control traffic signals.